The Effect of Servant Leadership and Job Satisfaction on Organizational Citizenship Behavior in TOYOTA Auto2000 Cirebon Employees - Rifqi Faizal Rahman; Agi Syarif Hidayat (PT FORMOSA CENDEKIA GLOBAL, 2026)
The purpose of this study is to analyze the influence of Servant Leadership and Job Satisfaction on Organizational Citizenship Behavior (OCB) in TOYOTA Auto2000 Cirebon Employees. The research method used an associative quantitative approach with a sample of 109 respondents. Data were collected through questionnaires and analyzed using multiple linear regression. The results of the study showed that Servant Leadership had a positive and significant effect on Organizational Citizenship Behavior, Job Satisfaction had a positive and significant effect on Organizational Citizenship Behavior, and both variables simultaneously had a significant effect on Organizational Citizenship Behavior with a contribution of 60.1%. The implications of this study emphasize the importance of a servant leadership style and job satisfaction fulfillment to encourage extra-role behaviors that support organizational effectiveness.